Maize intercropped with palisadegrass and pigeon pea in partial desiccation system - de Oliveira, Priscila; Kluthcouski, João; Favarin, José Laércio; Santos, Darliane de Castro (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess the viability of maize (Zea mays) cultivar BRS 1035 intercropped with palisadegrass (Urochloa brizantha) and pigeon pea (Cajanus cajan) in the partial desiccation system. The experiments were performed in the summer season of 2008/2009, in Santo Antônio de Goiás, GO and Ipameri, GO, Brazil, in a complete randomized block design, with five replicates. The treatments consisted of maize intercropped with palisadegrass and pigeon pea, with mineral nitrogen application on maize, on the day of its emergence, or 20 days after this event, with or without the application of a herbicide subdose on palisadegrass not desiccated. The viability of the partial desiccation system is dependent on the nitrogen fertilizer management of corn or on the growth control of nondesiccated palisadegrass rows.